PEFA, Public Financial Management, and Good Governance - World Bank Group (World Bank, Washington, DC, 2019)
The research is based on the PEFA framework and methodology for assessing public financial management performance and the data set that is generated from the PEFA assessments. The research quantified PEFA scores and aggregated them into overall scores which required developing assumptions on weighting scores, measures, and assessments. The research acknowledges methodological limitations of using the PEFA data set, including the assumptions. In general, the research follows the approach taken by previous researchers who have used PEFA data for quantitative analysis, but this does not eliminate the challenges that persist in transforming grades to numerical values and aggregating them. The time inconsistency issues and the limited number of observations also influenced the regression analysis using the PEFA data set. The team acknowledges that the PEFA data set was not designed for statistical analysis and that using it in quantitative regressions presents a series of econometric issues that cannot be fully resolved in this book, or in other papers which apply a similar approach. The research report builds on general recognition that PFM is important for development and recognizes that there is limited evidence based on the nontechnical determinants of PFM performance, as well as the outcomes of a good PFM system. The report therefore aims to bridge some of this gap between theory and practice using data on PFM performance from PEFA assessments. The report undertakes a closer examination of the key debates on what constitutes a good PFM system by providing an overview of the PEFA framework, and the data set that is generated through PEFA assessments, including its strengths and weaknesses. This was done to enable the research team to undertake quantitative analysis of the relationship between PFM performance and other governance indicators and outcomes.